An Empirical Analysis of the Perception of Management Students About Their Employment - Harsolekar, Dinesh D.; Munshi, Jyotsna (Prabandhan: Indian Journal of Management, 2018)
Management education is the most sought-after field for people all across the world. Most of the best and bright minds pursue management education because it is a sure way to highly paid jobs with great prospects for career advancement. Consequently, B-schools in India give a lot of importance to the student placements. When placement is most important, we need to address the serious employment challenges prevalent in the current market scenario. In this context, it was imperative to understand as to why students prefer one job offer over another. This study was an attempt to capture the perception of the students to identify the relative importance of certain parameters while evaluating their job offers. The perceptions were analyzed based on primary research on a sample of 167 students by administering the questionnaire to them.SPSS software was used for the detailed analysis. The results indicated that job profile and compensation were the two most important parameters considered by the students while evaluating their job offers. For 70% of the students, fixed part of the compensation was the most important, and desired functionality was the most important factor with respect to the job profile. The analysis was conducted on the data collected from a single B-school.